Social acceptability of the rehabilitation efforts conducted in an inactive mined-out area in Marinduque, Philippines - Katrine Mae B Mante; Nina M Cadiz (Journal of Degraded and Mining Lands Management, 2021)
The present study assessed the acceptability of the rehabilitation efforts conducted by the University of the Philippines Los Baños (UPLB) Bioremediation Team in an inactive mined-out area in Mogpog, Marinduque, Philippines from 2006 to 2016. A researcher-made semi-structured questionnaire was used to interview key informants, like members of the local government unit (LGU) of Mogpog, Marinduque, head of the Provincial of Environment and Natural Resources Office (PENRO), and selected residents of Barangay Ino and Capayang near the mining site. The selection of the respondents (n=112) was done through a stratified random probability sampling among residents ages 20 years old and above to determine their awareness and knowledge about the mined-out area before and after its rehabilitation. Interview with key informants revealed different functions towards the rehabilitation of the mined-out area. Results also showed that 59% of the respondents were aware of the rehabilitation efforts made on the site, and 98% of them strongly agreed on the presence and harmful effects of toxic chemicals in the area.   They also strongly agreed that the rehabilitation efforts had a positive impact on the environment, biodiversity and the community nearby. Interventions implemented by the government and other agencies are likely to succeed with the help of the nearby community and therefore, the same community can also be the best judge to determine the acceptability of the interventions.